2022
DOI: 10.1002/ppul.26118
|View full text |Cite
|
Sign up to set email alerts
|

Is implementation of a hospital pathway for high‐flow nasal cannula initiation and weaning associated with reduced high‐flow duration in bronchiolitis?

Abstract: Background High‐flow nasal cannula (HFNC) therapy is widely used for children with bronchiolitis, but its optimal role remains uncertain. Our institution created and later revised a clinical pathway guiding HFNC initiation and weaning. Methods A retrospective review of 1690 bronchiolitis encounters was conducted. Trends in the duration of HFNC and hours spent weaning HFNC as proportions of the monthly hospital length of stay (LOS) for bronchiolitis, hospital LOS, and escalation of care were compared using inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“… 26 , 27 Tarantino et al found that after implementing a bronchiolitis pathway with HFNC initiation and weaning guidelines, HFNC duration decreased without changing hospital LOS or escalation of care. 28 This finding conflicts with other studies that show that a decrease in HFNC treatment leads to a decrease in hospital LOS. 29 One explanation could be that HFNC has no impact on the course of bronchiolitis for m/m disease and, therefore, has no impact on LOS.…”
Section: Discussionmentioning
confidence: 61%
“… 26 , 27 Tarantino et al found that after implementing a bronchiolitis pathway with HFNC initiation and weaning guidelines, HFNC duration decreased without changing hospital LOS or escalation of care. 28 This finding conflicts with other studies that show that a decrease in HFNC treatment leads to a decrease in hospital LOS. 29 One explanation could be that HFNC has no impact on the course of bronchiolitis for m/m disease and, therefore, has no impact on LOS.…”
Section: Discussionmentioning
confidence: 61%
“…The next steps include efforts to further reduce the overutilization of HFNC, given our still high postintervention rates based on the literature. 12 , 22 We intend to incorporate a trial off of HFNC for incoming transported patients arriving with a mild to moderate respiratory score while on HFNC.…”
Section: Discussionmentioning
confidence: 99%